PENGUATAN PENGETAHUAN TAHAPAN PRODUKSI FILM PENDEK PADA EKSTRAKURIKULER SINEMATOGRAFI SEKOLAH MENENGAH ATAS - Santoso, Ady (PPPM POLTESA, 2023)
The community service activities carried out depart from the importance of the existence of extracurriculars in high schools, where the activities carried out by these extracurriculars become a forum for developing the talents and interests of students who are members of an extracurricular. The problem that arises from the existence of a cinematography extracurricular at Titian Teras Jambi State High School is the lack of knowledge among its members regarding the stages of the short film production process. Departing from this problem, community service activities with partners who are members of the cinematography extracurricular at Titian Teras Jambi State High School are carried out using the following methods: (1) delivering material; (2) training in the use of short film production equipment; and (3) simulating the short film production process. The findings obtained from the implementation of this community service activity are: (1) extracurricular members are increasingly aware of the stages of the short film production process; (2) extracurricular members increasingly know how to operate short film production equipment; (3) extracurricular members are able to simulate the short film production process. The conclusion of the community service activities that have been carried out is that the members of the cinematography extracurricular program have become more aware of the stages of the short film production process, they are increasingly able to operate short film production equipment, and are able to simulate the short film production process.